Spiral arms in scattered light images of protoplanetary discs: are they the signposts of planets? - Juhász, Attila; Pohl, Adriana; Dullemond, Cornelis (Arxiv, 2015)
One of the striking discoveries of protoplanetary disc research in recent years are the spiral arms seen in several transitional discs in polarised scattered light. An interesting interpretation of the observed spiral features is that they are density waves launched by one or more embedded (proto-)planets in the disc. In this paper we investigate whether planets can be held responsible for the excitation mechanism of the observed spirals. We use locally isothermal hydrodynamic simulations as well as analytic formulae to model the spiral waves launched by planets. Then H-band scattered light images are calculated using a 3D continuum radiative transfer code to study the effect of surface density and pressure scale height perturbation on the detectability of the spirals. We find that a relative change of about 3.5 in the surface density is required for the spirals to be detected with current telescopes in the near-infrared for sources at the distance of typical star-forming regions (140pc). This value is a factor of eight higher than what is seen in hydrodynamic simulations. We also find that a relative change of only 0.2 in pressure scale height is sufficient to create detectable signatures under the same conditions. Therefore, we suggest that the spiral arms observed to date in protoplanetary discs are the results of changes in the vertical structure of the disc (e.g. pressure scale height perturbation) instead of surface density perturbations.